A simple and universal strategy for preparing external stress-free two-way shape memory polymers by making use of the chemical crosslinkages derived from peroxide initiator - L. F. Fan; Y. N. Huang; M. Z. Rong; M. Q. Zhang (eXPRESS Polymer Letters, 2020)
In the present work, a new strategy for preparing authentic two-way shape memory polymer was proposed by using a conventional crosslinked polyurethane (PU) containing crystalline poly(ε-caprolactone) (PCL) as the proof-ofconcept material. Lauroyl peroxide (LPO) was added as a chemical crosslinker for inducing secondary crosslinking during the programming. Having been stretched and heat treated without additional ingredients and chemicals, the trained PU showed the desired two-way shape memory effect. The crosslinking network created by LPO was successfully converted into internal stress supplier, which represents the core progress of this research. As the temperature changed, the reversible melting/re-crystallization of the crystalline phases elaborately cooperated with the compressed crosslinking network, leading to the implementation of two-way shape memory effect. Through the optimization of the LPO quality, an average reversible strain of up to ~21% in the direction of stretching was measured. In principle, all semi-crystalline polymers can be imparted with two-way shape memory effect following the above-proposed method. Given the great convenience of material selection, preparation, programming and application, the current research may have opened a new way for the production and usage of the smart materials in practice.